ChemInform Abstract: Synthesis, Crystal Structure, and Physical Properties of Sr2FeOsO6. Issue 33 (25th July 2013) - Paul, Avijit Kumar; Jansen, Martin; Yan, Binghai; Felser, Claudia; Reehuis, Manfred; Abdala, Paula M.
Abstract Polycrystalline Sr2FeOsO6 is prepared by solid state reaction of a stoichiometric mixture of SrO2, OsO2, and Fe2O3 (corundum containers in sealed quartz tubes, 1.